323 Is daytime napping a risk factor for persistent insomnia symptoms?. (3rd May 2021) - Pereira, Rui; Hartescu, Iuliana; Morgan, Kevin; Jackson, Robin; Ellis, Jason; Morales, Knashawn; Perlis, Michael
Abstract: Introduction: Napping, episodes of short daytime sleep separated from the main sleep period, can compensate for the detrimental effects of inadequate night-time sleep or, as 'siestas', may form an integral part of personal sleep-wake schedules. Napping may also precipitate or perpetuate insomnia symptoms through the erosion of homeostatic sleep pressure at night. Using longitudinal data, these analyses were designed to evaluate links between daytime napping styles and the incidence of persistent insomnia symptoms, in a sample of middle aged and older adult good sleepers at baseline. Methods: 567 participants (65% female; >35 years old) were sub-sampled from the NITES cohort (Perlis et al, 2019). All were self-rated good sleepers, reporting typical sleep latencies (5 nights/week) and WASO durations of = 1 nap/baseline period) or habitual (>= 2 naps/week). 'Persistent insomnia symptoms' cases reported sleep initiation and/or maintenance complaints on >= 3 nights/week for at least two consecutive weeks. Relationships between nap categories and the incidence of persistent insomnia symptoms arising in months 4–12 of the study were assessed in logistic regression models adjusted for age, gender, employment status and depression. Risk is expressed as the odds ratio (OR) with 95% confidence interval (CI). Results: Prevalence rates for ever/habitual napping were 57% and 10%. Unemployed status and aged 50+ significantly increased habitual nap probability. The 1-year incidence of persistent insomnia symptoms was 5.6%. In logistic regression models, 'ever' napping was associated with an almost 3-fold increase in the risk of developing persistent insomnia symptoms (OR=2.994; 95% CI 1.244–6.969; p=.014). When the logistic regression model was rerun with habitual napping, the risk attenuated substantially (OR = 1.4, 95% CI .592–3.163; p=.463). Conclusion: These results suggest that napping patterns serve as a marker for insomnia symptom development, with haphazard non-habitual napping patterns associated with significantly greater risk. Support (if any): RP: Loughborough University doctoral studentship; MP: K24AG055602 & R01AG041783 (NITES).